Explosion Load Characteristics of Fuel—Air Mixture in a Vented Chamber: Analysis and New Insights - Xingxing Liang; Yaling Liao; Zhongqi Wang; Huaming An; Junjie Cheng; Chunliu Lu; Huajiao Zeng (Energies)
The advances in research on the explosion load characteristics of the fuel–air mixture in vented chambers are reviewed herein. The vented explosion loads are classified into three typical types based on this comprehensive literature research. These models are the accumulation load model, attenuation load model, and interval jump load model. The characteristics of the three different typical vented explosion load models are analyzed using Fluidy-Ventex. The research results show that overpressure is largely determined by methane concentrations and vented pressure. The turbulent strength increased from the original 0.0001 J/kg to 1.73 J/kg, which was an increase of 17,300 times, after venting in the case of a 10.5 v/v methane concentration and 0.3 kPa vented pressure. When the vented pressure increased to 7.3 kPa, the turbulent strength increased to 62.2 J/kg, and the overpressure peak correspondingly increased from 69 kPa to 125 kPa. In the case of the interval jump load model, the explosion overpressure peak tends to ascend when the intensity of the fluid disturbance rises due to the venting pressure increasing at a constant initial gas concentration. When the venting pressure reaches tens of kPa, the pressure differential increases sharply on both sides of the relief port, and a large amount of combustible gas is released. Therefore, there is an insufficient amount of indoor combustible gas, severe combustion is difficult to maintain, and the explosion load mode becomes the attenuation load model.